A Comparative Study on Teachers’ Perceptions Towards Principal’s Instructional Leadership According to Their Demographics in Ush Private School, Mandalay, Myanmar - Yu, Kyi Kyi; Ye, Yan; Kanjanaphoomin, Jane (Scholar: Human Sciences, 2019)
The main purpose of this study was to identify the demographic profiles of teachers, to determine Teachers’ Perceptions towards Principal’s Instructional Leadership, and to compare Teachers’ Perceptions towards Principal’s Instructional Leadership at USH private School Mandalay according to their gender, age, educational background and work-experiences in 2017. A total of 53 teachers (23 male and 30 female) from USH private school Mandalay completed the questionnaire, it was designed to identify the Teachers’ demographics and their perceptions towards principal’s Instructional Leadership. The questionnaire was adopted from Murphy & Hallinger (1985) Principal’s Instructional Management Range Scale (PIMRS). This research study was designed as a quantitative and comparative study. The data from this research was analyzed by frequency & percentage, mean and standard deviation, Independent Sample t-test and One-Way ANOVA. The study found that the level of Teachers’ Perceptions towards Principal’s Instructional Leadership was moderate. At the significance level .05, there were no significant differences on Teachers’ Perceptions towards Principal’s Instructional Leadership according to their gender, age, Educational background and work-experiences in USH private school Mandalay, Myanmar. This research study would give valuable insight into the role of Instructional Leadership support in shaping teachers, principal and teacher-principal relationship, student achievement and school improvement. It recommended that the Principal must involve his/her Instructional Leadership management on teachers and students such as protecting Instructional time, communicating school goals, monitoring student progress.